Influência da adição de um fundente sintético no mecanismo de coloração final de revestimentos cerâmicos - Santos, Geocris Rodrigues dos (2011)
The presence of iron oxide in ceramic tile mass contributes to the reddish color firing of the products leading to a lower aggregate value, not to be regarded as a "noble" ceramic. However, the use of raw materials with low levels of iron oxides (Fe2O3) is economically unfeasible in Brazil, since most of the deposits have iron compounds as mineral component. Thus, the objective of this work was that of studying the interaction of the iron element in the final color mechanism of the ceramic tile mass. For this purpose, we have employed several compositions of stoneware tile mass making use of natural raw materials, and a synthetic flow. This flow is constituted of a vitreous phase of the silicates family obtained by fusion/solidification of oxides and carbonates. Such flow influences the color ceramic mass during the process of sinterization modifying the red color firing into whiteness. That occurs when added in compositions containing clays with high levels of iron oxides. Beyond the physical properties obtained from the different employed compositions, we have also used other characterization techniques in order to study the phenomenon, such as: X-ray photoelectron spectroscopy (XPS), Mössbauer spectroscopy, Xray diffraction (XRD), quantitative analysis of phases by Rietveld method and scanning electron microscopy (SEM). The results have shown that the synthetic flow acts as a modifying agent for color when incorporated with values above 33%wt. in the compositions and temperature at 1,100°C . The color firing modification occurs because the chemical composition of the synthetic flow assists to form new iron compounds, thus making the final color firing light. By using this mechanism in the ceramic substrates, the stoneware tiles can be manufactured using low cost clays with high levels of iron oxides. This method proved to be an economical as well as commercial strategy for the ceramic tile industries.